Regulation reform process and perception in the Palestinian water sector. Issue 7 (3rd October 2018) - Nour, Raya; Al-Saidi, Mohammad
ABSTRACT: The study analyzes the regulation reform process of the Palestinian urban water sector. It introduces the holistic reform agenda and examines the water supply sector's performance and regulation challenges. The study also evaluates the perception of water service providers regarding the regulation reforms. Collected evidence indicates a dominant interpretation of the regulation concept based on rules and legislation, coupled with a neglect of aspects like monitoring, economic regulation and managerial accountability. The lack of awareness of the benefits of these aspects for service providers can increase resistance to reform and reduce willingness to participate in implementing comprehensive sector regulation.